Wspieranie innowacji technicznych w skali lokalnej na przykładzie Technologie-Zentrum Zittau (TZZ) - Adamczuk, Franciszek (Technical Innovations Support on the Local Scale on Example of Technologie-Zentrum Zittau (TZZ), 2008)
The point of the article is to show the means and results of technical innovations support in Europe. As an example Technologie-Zentrum Zittau (TZZ) was chosen. It is a part of business surrounding in Nysa Euroregion. The article tries to describe which experience of the TZZ's activity may be transferred into Polish realities. Some of recommendations and suggestions are created in this case. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 29-37